2008
DOI: 10.1002/eej.20639
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative allocation of SVR and SVC for voltage fluctuation in case of connecting distributed generators

Abstract: SUMMARYThis paper presents a method for cooperative allocation of step voltage regulators (SVRs) and static var compensators (SVCs) when some distributed generators (DGs) are installed in a distribution system. In the proposed method, reactive tabu search (RTS) with multiple structures and functions is applied. First, the allocations of the SVRs are selected optimally and then the tap positions of the SVRs are optimized by the RTS. Finally, the locations of the SVC are chosen in order to enhance the voltage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…하지만 분산전원의 출력으로 인한 역조류와 인근 모선의 전압상승 문제를 해결하기 위해서는 분산전원을 고 려한 전압 제어 기기의 운영과 계획에 대한 새로운 해결책 이 마련되어야 한다 [6][7][8][9][10][11][12][13].…”
Section: 서 론unclassified
“…하지만 분산전원의 출력으로 인한 역조류와 인근 모선의 전압상승 문제를 해결하기 위해서는 분산전원을 고 려한 전압 제어 기기의 운영과 계획에 대한 새로운 해결책 이 마련되어야 한다 [6][7][8][9][10][11][12][13].…”
Section: 서 론unclassified
“…Venkateswarlu & al [6] investigated the impact of a SVC and a DG on a distribution network and found that the optimal placement of a SVC and a DG significantly improves the ability of a transfer of an electrical network. JUNJIRO SUGIMOTO proposed in [7] the taboo search method to search the optimal position of a SVC and SVR in an electrical installation already constituted by a DG. M. A.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain customer voltage within allowable limit, tap operation of SVR installed in primary feeder is usually carried out according to the pre-designed setting value of delay time ranging from 30 to 150 sec. Existing papers regarding SVR operation are only dealt with optimal voltage regulation methods in distribution systems with PV system by SVR to deliver reasonable voltage to as many customers as possible [1][2][3][4][5]. However, there are not considered that power quality problems such as under voltage and over voltage could be occurred during the delay time of SVR.…”
Section: Introductionmentioning
confidence: 99%